EFFECTS OF FILLER HYBRIDIZATION ON THE MECHANICAL PROPERTIES OF NR/SBR/EPDM RUBBER BLENDS - Soh, T.C.; Mohamad, N.; Ahsan, Q.; Abd Manaf, M.E. (Journal of Advanced Manufacturing Technology (JAMT), 2015)
Hybridization of active fillers is one of the techniques utilized to enhance rubber properties. This study highlights the effects of filler hybridization on the mechanical properties of an industrial applied natural rubber/styrene butadiene rubber/ethylene propylene diene terpolymer (NR/SBR/EPDM) Rubber Mat compound reinforced by non-black fillers. Initially, three different rubber compounds were prepared; i) calcium carbonate (CaCO3)-filled NR [CaCO3NR] as reference sample, ii) precipitated silica (PSi)-filled NR/SBR/EPDM [PSiBR], and iii) calcined clay (ClCy)-filled NR/SBR/EPDM [ClCyBR]. From these compounds, composites of NR/SBR/EPDM were prepared. The ratio of PSi:ClCy was varied to study the effects of filler hybridization. CaCO3 was added for cost advantage industrially and its level was fixed. It was found that inclusions of ClCy and PSi individually and their hybridizations show higher tensile and tear strengths than the reference sample. Particularly, the largest improvement was found with the amount of ClCy which is higher than PSi. A ratio of PSi:ClCy in this particular range (1:2 to 2:3), seems to provide the optimum packing factor for good interaction between the fillers. SEM analysis suggests that better dispersion and packing of fillers due to size and shape of hybrid fillers play an important role in improving the composite properties.